Religie a biznes - Gasparski, Wojciech (Annales. Etyka w Życiu Gospodarczym, 2008)
Paper is devoted to the ethical issues of business as considered from the points of view of main religions: Christianity – Catholicism and Protestantism – as well as Judaism and Islam. Ethos of Hinduism and the Caux Round Table efforts to disseminate its principles in cooperation with the world of religion are also mentioned. John Paul II’s and Benedict XVI’s addresses to business leaders are recalled. Suggestion to establish partnership relations between clergymen and business people is pointed out.